Minding the Data-Gap Trap: Exploring Dynamics of Abundant Dolphin Populations Under Uncertainty - Ashe, Erin; Williams, Rob; Clark, Christopher; Erbe, Christine; Gerber, Leah R.; Hall, Ailsa J.; Hammond, Philip S.; Lacy, Robert C.; Reeves, Randall; Vollmer, Nicole L. (Frontiers in Marine Science, 2021)
Preventing declines in common species is key to sustaining the structure and function of marine ecosystems. Yet for many common marine mammals, including oceanic dolphins, statistical power to detect declines remains low due to patchy distribution and large variability in group sizes. In this study, Population Viability Analyses (PVA) were used to predict the dynamics of four oceanic dolphin populations off the US West Coast: eastern North Pacific long-beaked common dolphins (Delphinus delphis capensis), short-beaked common dolphins (D. delphis delphis), Pacific white-sided dolphins (Lagenorhynchus obliquidens), and “offshore” common bottlenose dolphins (Tursiops truncatus). We calibrated the PVAs with life-history tables, studies on proxy species, and stock assessment reports. We explored the sensitivity of populations to demographic variation and predicted how stocks may respond to changes in three sublethal threats (prey limitation, ocean noise, and chemical pollution) and one lethal threat (fisheries bycatch). We found the most serious predicted declines in long-beaked common dolphins, which showed the lowest birth rate. Worryingly, most threat scenarios resulted in declines that would not be detected by existing monitoring programs, which are among the most data-rich surveys of their kind. The cumulative effects of the three sublethal stressors exceeded the effect of the one lethal stressor (fisheries bycatch). To implement pro-active management and monitoring programs, anticipating which cetaceans may be more at risk and which anthropogenic threats could cause declines is paramount. Our study highlights the value of model testing with PVAs when monitoring data are poor, thereby identifying future priorities for research, monitoring, and management.